2020
DOI: 10.1111/aji.13296
|View full text |Cite
|
Sign up to set email alerts
|

Soluble immune checkpoints CTLA‐4, HLA‐G, PD‐1, and PD‐L1 are associated with endometriosis‐related infertility

Abstract: Problem: Soluble immune checkpoint molecules constitute the emerging novel mediators in immune regulation. Their role in the pathogenesis of endometriosis has not been fully addressed. In this study, we aimed to investigate the relationship between the clinical manifestation of endometriosis-associated infertility and the level of four soluble immune checkpoints: sCTLA4, sHLA-G, sPD-1, and sPD-L1. Method of study: The soluble immune checkpoint concentrations in serum and peritoneal fluid from 88 patients who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 25 publications
(40 reference statements)
3
31
0
Order By: Relevance
“… [ 143 ] Endometriosis Elevated level of sPD-L1 in the serum and peritoneal fluid of patients with endometriosis vs. control. [ 144 ] Idiopathic pulmonary fibrosis (IPF) Elevated concentrations of sPD-L1 in the serum of IPF patients compared to healthy population. [ 27 ] Immune thrombocytopenia (ITP) Decreased levels of sPD-L1 in patients with newly diagnosed ITP compared to patients with chronic ITP.…”
Section: Soluble Pd-l1 Beyond Cancermentioning
confidence: 99%
See 1 more Smart Citation
“… [ 143 ] Endometriosis Elevated level of sPD-L1 in the serum and peritoneal fluid of patients with endometriosis vs. control. [ 144 ] Idiopathic pulmonary fibrosis (IPF) Elevated concentrations of sPD-L1 in the serum of IPF patients compared to healthy population. [ 27 ] Immune thrombocytopenia (ITP) Decreased levels of sPD-L1 in patients with newly diagnosed ITP compared to patients with chronic ITP.…”
Section: Soluble Pd-l1 Beyond Cancermentioning
confidence: 99%
“…Elevated levels of sPD-L1 have been measured in the serum and the peritoneal fluid of endometriosis patients compared to controls. The protein could thus represent a biomarker for endometriosis [ 144 ]. In cases of preeclampsia (a pregnancy complication characterized by high blood pressure and damages to organs such as the liver and kidneys), the maternal sPD-L1 level can increase a little but it is essentially sPD-1 levels which are significantly enhanced in preeclamptic women compared to normotensive pregnant women [ 185 ].…”
Section: Soluble Pd-l1 Beyond Cancermentioning
confidence: 99%
“…In a study on endometriosisassociated infertility, Santoso B et al have investigated the level of soluble(s) CTLA, sPD-1, sPD-L1, and HLA-G in endometriosis. HLA-G may act similar to IC molecules presented on cytotoxic T cells (CD8+T cells), they have found HLA-G accompanied sPD-L1 and sCTLA-4 may implicated in the pathological mechanisms of endometriosis-related infertility (39). Schwich E et al demonstrated that sHLA-G1 significantly increased the frequency of ILT-2 receptors on CD8+ T cells and might be involved with other IC molecules to generate an immunosuppressive or exhausted phenotype (40).…”
Section: Bio-functional Character Of Hla-gmentioning
confidence: 99%
“…For example, immunotherapy either by targeting T cells or administration of immune checkpoint inhibitors has emerged as a promising treatment for chronic inflammatory diseases such as rheumatoid arthritis (Wei et al, 2020) and difficultto-treat cancers. As our understanding of the role(s) of T cells and other immune cells in the etiology of endometriosis expands, we may soon be able to capitalize on the remarkable progress made by developing and implementing immunotherapy as an endometriosis treatment (Santoso et al, 2020). Our own work that identified the mechanisms responsible for the altered metabolic phenotype of the peritoneal mesothelial cells in women with endometriosis has allowed us to investigate the repurposing of drugs that have impact on lactate production (Horne et al, 2019a).…”
Section: Discussionmentioning
confidence: 99%